Evolution of the free volume during water desorption in thermoplastic starch/citric acid films: In situ positron annihilation studies. (15th June 2023) - Estevez-Areco, Santiago; Macchi, Carlos; Guz, Lucas; Goyanes, Silvia; Somoza, Alberto
Abstract: The effect of citric acid (CA) concentration and water content on the free hole volume of thermoplastic cassava starch films (TPS) was studied. To this aim, continuous in situ positron annihilation lifetime spectroscopy measurements were performed at fixed moisture content and during water desorption. The results show that the increase in CA concentration leads to wider free hole volume distributions with lower mean values. During water desorption, the mean values and width of such distributions systematically decrease with the exposure time, and the evolution of the hole volumes was well-described using the Kohlrausch-Williams-Watts function. The water vapour permeability was significantly higher in films incorporating 5 % (w/w) of CA, in line with the more open network of this material that was revealed in the hole volumes distribution. The Young's modulus of all the developed films increased significantly after partial water desorption, which was attributed to the plasticizer loss reflected in a decrease in the mean hole volume value (between 4 % and 13 %). This work evidences that the control and report of the relative humidity are essential when testing TPS-based films, as their nanostructures are strongly dependent on external conditions. Graphical abstract: Unlabelled Image